Qur'an Whiz: Developing an Android-Based Application to Enhance Qur'an Memorization Skills for Elementary School Students - Djainudin, Hamdhan; Saputra, Apry Aditya; Rahmat, Nazaludin Nur; Aprilio, Triandi (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2025)
Post-COVID-19, Islamic religious education faced challenges due to mosque restrictions and suspended Qur'anic programs, reducing youth interest in memorization. Technological distractions also prompted shifts in teaching methods to adapt to digital advancements. This study aims to develop the Qur'an Whiz educational game application for Qur'anic memorization using the Takrir method, designed specifically for the Android platform. The research adopted the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) as its methodological framework. Iterative testing and validation processes involving material, design, and media experts were conducted to refine the application and ensure its effectiveness and user engagement. The activities carried out at the analysis stage are collecting data through interviews and observations, related to existing problems. Furthermore, implementation is carried out by testing the application in the community, students, material experts, design experts, and media experts. After testing and implementing the product, the final stage is evaluating and perfecting the